Equipo deportivo del Colegio San Pedro Claver (1910)
Aparecen de izquierda a derecha: Jesid Trebert Orozco, Lázaro Gómez, José M. Rugeles, Luis Miguel Ortiz, Peña, Luis F. Villamizar, Quintin Gustavo Gómez Rodríguez, Francisco Angulo C., Saul Amezquita, Francisco Puyana Menéndez y Carlos Enrique Ardila